Relationship of Ability of Family Caregivers and Society’s Stigma to Prevent Relapse and Improve the Quality of Life for People with Mental Disorders - Widyowati, Agustin; Murti, Bhisma; Sudiyanto, Aris (Open Access Macedonian Journal of Medical Sciences, 2021)
People with mental disorders will experience a relapse even after 1 month of getting treatment or care from a health facility. The high recurrence rate can cause a decrease in quality of life. Efforts to prevent recurrence by involving family caregivers and reducing stigma from the community. This study aims to analyze the relationship between the ability of family caregivers and community stigma to prevent recurrence and improve the quality of life of people with mental disorders. This study used a cross-sectional approach. The research location is in Kediri Regency, East Java, Indonesia. Sampling was done by using the multistage random sampling technique. The number of samples is 76 respondents. The variables in this study were the ability of family caregivers, community stigma, disease recurrence, and quality of life for people with mental disorders. The data were analyzed using path analysis with the help of STATA 13. There is a relationship between the ability of family caregivers and community stigma to prevent recurrence and improve the quality of life of people with mental disorders.